ПОДОЛАННЯ КОНФЛІКТІВ У СИСТЕМІ “УЧИТЕЛЬ-УЧЕНЬ” ЗАСОБАМИ ГУМАНІСТИЧНОГО ПІДХОДУ ДО ОРГАНІЗАЦІЇ ПЕДАГОГІЧНОГО ПРОЦЕСУ (Педагогіка вищої та середньої школи, 2006)
The possibilités of the humanistic approach to the organization of pedagogikal process in overcoming the conflict relations between the teacher and tne pupil are considered in this article.